Monumentos, memória e cidade: estudo de caso em Belo Horizonte - Eduardo Henrique de Paula Cruvinel (2012)
The urban spaces save and accumulate a variety of events that will mark significantly its evolution. These will, gradually, adding up, passing to represent the memory of the city and its society, storing a number of valuable cultural references. In Belo Horizonte, built in the nineteenth century, its possible to find monuments that tell the story not only of capital but of the entire state of Minas Gerais. The monument, raised as a material representation of memory, by reflections that ask about its specificity in relation with the space, provides an investigation of the tensions and conflicts in this interaction. It is based on the understanding of monuments as evidences that the formation of the city can be studied and that the government starts to worry about the preservation of heritage. The interdisciplinary field of studies related to monuments enables breakthroughs in the discussions thanks to the contributions of each theoretical area involved, as will be presented in this dissertation.